If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = 7x + 1 Reorder the terms: 5 + 6x = 7x + 1 Reorder the terms: 5 + 6x = 1 + 7x Solving 5 + 6x = 1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 5 + 6x + -7x = 1 + 7x + -7x Combine like terms: 6x + -7x = -1x 5 + -1x = 1 + 7x + -7x Combine like terms: 7x + -7x = 0 5 + -1x = 1 + 0 5 + -1x = 1 Add '-5' to each side of the equation. 5 + -5 + -1x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 1 + -5 -1x = 1 + -5 Combine like terms: 1 + -5 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 6d-4=12 | | 3k^2+72=32k | | 10x+4=14x | | -50=-18-2x | | 4y+5=17 | | 2x+13-x+13=4 | | 2x^8=17 | | x/6=-3 | | 1x/12+4=-17 | | 25m^2-1=0 | | 2x^2-3x+1= | | 12x=-48 | | X^2-18x+81=7 | | 4x^2-8x-90=0 | | 1x/12+4=17 | | 26=-6y+6+2y | | 5x^2-24x-5= | | 5x^2+60x=-70 | | 3x^2+2x-1= | | 2x^2+8=23 | | 12t-1(7-3t)=-8t-30 | | 4(s+22)=4(s+12) | | x^3+(2x^2)+(4x)+2=0 | | 8x+5y=5x+2y | | x^3+2x^2+4x+2=0 | | 8f=56 | | 2y^2-14y+12=0 | | 2x+4=-3x+7 | | 2j-5=k | | 5x^2+13x+6= | | 8x-7=33 | | -10+3(x)=26 |